The Strategy of Blitar Regency’s Government to Increase the Role of Health Center Services in Dealing with Covid-19 Pandemic - Susi Narulita Kumala Dewi; M.R. Khairul Muluk; Romy Hermawan (Sekolah Pascasarjana Universitas Brawijaya, 2021)
In recent years, the issue of health services has become a national public spotlight in Indonesia. Especially since the Corona Virus Disease (COVID-19) pandemic emerging, where the role of health institutions around the community is very important. This study aims to determine the quality of PUSKESMAS as a heath institution with strategic role in dealing with the COVID-19 pandemic. By the descriptive method which is combined with quantitative approach, this research was conducted to all PUSKESMAS in Blitar regency. While the reason of Blitar regency has been chosen in this study was due to their succeed for decreasing rate of COVID-19 epidemic in several areas in Blitar. Therefore, the discussion in this study will be aimed at analyzing the strategies used by related actors in reducing the spread of COVID-19 in Blitar regency. The results of this study indicates that the overall quality of PUSKESMAS in Blitar district is not good enough. However, with appropriate strategy carried out by the Blitar Government, it can maximize these limitations. Thus at the end, it may resulting total reduction in the spread of COVID-19 in several areas.